Semioquímicos e comunicação sonora em formigas cortadeiras (Hymenoptera: Formicidae) - Carlos, Amanda Aparecida [UNESP] (2013)
The leaf-cutting ants (Atta and Acromyrmex) are considered a significant plague in the neotropics, demanding efficient methods of control in order to contain the detrimental impact. Studies on their biology, ecology and behavior are of vital importance for the understanding of these insect societies, providing information on the adequate handling and control of these species. Regarding this aspect the use of cuticular hydrocarbons and stridulation of these ants was proposed as tool for the identification of four spcies of the genus Atta spp. The interaction of A. sexdens rubropilosa workers with wax derived epicuticular hydrocarbons from native scrubland (“cerrado”) plants and one exotic plant as well as with tricomes from V. sebifera was observed. Furhter on, still using A. sexdens rubropilosa as a model, its stridulatory pattern was compared with two intermediate species of the Attini tribe. The acoustic pattern of distinct castes (queens, non fertilized females, males, soldiers and workers) of A. sexdens rubropilosa and the vibrations of Atta laevigata during the processing of vegetal substrate on the symbiotic fungus were described as well. With this data it was possible to infer the specificity of cuticular hydrocarbons for the species estudied (Atta capiguara, Atta sexdens rubropilosa, Atta bisphaerica and Atta laevigata). The interaction of epicuticular hydrocarbons of the studied plants with A. sexdens rubropilosa workers showed that, although chemical stimulus decides the ants` choice to carry a certain plant, the hydrocarbons were not the decisive compounds for this selection. The acoustic patterns of the intermediate ant species are distinct and both species acoustically differ from A. sexdens rubropilosa, the most derived species investigated. It was not possible to determine a species-specific acoustic pattern for non fertilized females, while in A. sexdens the reproducing castes showed clear separation from the workers...